(untitled) (Bangladesh Journal of Agricultural Research, 2012)
The experiment was conducted for two consecutive rabi seasons of 2005-06 and 2006-07 at the Regional Agricultural Research Station (RARS), BARI, Jamalpur to find out an optimum dose of sulphur for yield maximization of garlic cv. Jamalpur local. There were six levels of sulphur viz., 0, 15, 30, 45, 60, and 75 kg/ha. A control treatment was in the experiment. The experiment was laid out in randomized complete block design with three replications. The fertilizer package N150P60K120Zn4 B1 kg/ha was applied to each plot as blanket dose. Results revealed that most of the growth and yield parameters increased progressively with increasing rate of sulphur application. Bulb yield increased with successive increase in the level of sulphur up to 45 kg/ha and thereafter decreased. The highest bulb yield (7.05 t/ha in 2005-06 and 7.22 t/ha in 2006- 07) was achieved at 45 kg S/ha and the control treatment receiving no fertilizer had the lowest yield (3.21 t/ha in 2005-06 in and 3.26 t/ha in 2006-07). The yield benefit for 45 kg sulphur per hawas 34.2% in 2005-06 and 40.0% in 2006-07 over no sulphur. Sulphur at 45 kg/ha produced 54.5% and 54.9% higher yield over control treatment in both the years. The optimum and economic dose of sulphur for the yield of garlic were 44.0 and 43.6 kg/ha, respectively. DOI: http://dx.doi.org/10.3329/bjar.v36i4.11751 Bangladesh J. Agril. Res. 36(4): 647-656, December 2011